Strategi Manajemen Sumber Daya Manusia dalam Meningkatkan Keunggulan Bersaing Perusahaan - Aprinawati Aprinawati; Sandriana Aisya Putri; Farhan Abdullah; Ryan Alfandi; Putri Elma (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Human resource management helps organizations achieve their short-term and long-term goals by aligning with overall business strategy. For this reason, the aim of writing this paper is to understand the relationship between Human Resource Management (HRM) and business strategy and provide an overview of good employee training and development to increase productivity in companies. The research method is qualitative with library study data collection techniques. Based on the study, it is known that the assumption of a close relationship between business strategy and HRM methods is based on contingency theory. This theory underlines that human resource management methods are chosen according to the type of competitive strategy adopted by the business. A well-crafted business strategy aligns with the core mission and vision and acts as a roadmap for profitability, competitiveness and sustainable growth. Training and development that influences employee productivity has increased the welfare of the company and also helped the company's prosperity by considering the planning and implementation of workforce training and development at the public level.